PENGARUH SOSIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN DIMEDIASI OLEH BRAND AWARENESS PADA FUELS COFFEE KOTA BANDUNG - Kurniawan, Muhammad Aldy; Fitriani, Efi (STIE Semarang, 2024)
The culinary business is one sector that influences the growth of the tourism industry. Over time, the culinary business has been growing rapidly, including in Bandung City, where competition among culinary business entrepreneurs is becoming increasingly fierce. Fuels Coffee shop must be able to innovate to determine the right marketing strategy. One way is by utilizing social media marketing to build consumer brand awareness, thereby facilitating the purchase decision process. This study aims to determine the effect of social media marketing on purchase decisions mediated by brand awareness at Fuels Coffee in Bandung City. The type of research used is quantitative research with a descriptive verification approach. The data collection technique used in this study is primary data, with the method of distributing questionnaires to 100 respondents of Fuels Coffee in Bandung City. The data analysis technique uses path regression analysis and the Sobel test. The results show that social media marketing has a positive and significant effect on brand awareness and purchase decisions, and brand awareness positively and significantly mediates the relationship between social media marketing and purchase decisions.